A presença das religiões na EMARC de Valença - Lima, Ruy D'oliveira (2009)
This research presentes educational and theological reflections developed in an rural school on the countryside of Bahia state. The presence of religions in the EMARC of Valença is the focus of this study. Naturally, the issue is not being exhausted here due to its complexity and two important categories: education and religion. However, here is our contribution towards the state of the art, like a seed, a provocation for other studies on the issue. As we carry out this study, the discussion on the exhibition of religious symbols in public spaces is occupying the media, the courts and Brazilian universities, being a subject for meetings, roundtables and specific congresses on the question of the secularity of the State, civil religion and theology. These aspects were dealt with during the present research. The research report was constructed in three chapters, under the following titles: (1) Getting to Know the People, the place and the school; (2) Apple: a critical analysis of education, and (3) Religion, State and Education. In the first chapter was characterized the object of research, its idiosyncrasies and the history of the people who live in the region. The second chapter was devoted to deal with the theoretical underpinning the work. In the third and last one, we present results and analyses underlying them.